2017
DOI: 10.2147/ndt.s115261
|View full text |Cite
|
Sign up to set email alerts
|

Physical factors that influence patients’ privacy perception toward a psychiatric behavioral monitoring system: a qualitative study

Abstract: BackgroundPsychiatric patients have privacy concerns when it comes to technology intervention in the hospital setting. In this paper, we present scenarios for psychiatric behavioral monitoring systems to be placed in psychiatric wards to understand patients’ perception regarding privacy. Psychiatric behavioral monitoring refers to systems that are deemed useful in measuring clinical outcomes, but little research has been done on how these systems will impact patients’ privacy.MethodsWe conducted a case study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The study location was mostly in Saudi Arabia (57.5%, n=140). Other study locations included the United States (1.9%, n=3) [22][23][24], Malaysia (1.9%, n=3) [25][26][27], and Canada (0.8%, n=2) [28,29]. The majority of publications (35.1%, n=85) used quantitative methods, and the minority of publications (9.1%, n=22) used mixed methods.…”
Section: Publication-based Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study location was mostly in Saudi Arabia (57.5%, n=140). Other study locations included the United States (1.9%, n=3) [22][23][24], Malaysia (1.9%, n=3) [25][26][27], and Canada (0.8%, n=2) [28,29]. The majority of publications (35.1%, n=85) used quantitative methods, and the minority of publications (9.1%, n=22) used mixed methods.…”
Section: Publication-based Analysismentioning
confidence: 99%
“…For publications in 2000-2009, data sources used were surveys or questionnaire data [30], patient or medical data [31][32][33], clinical or health care research datasets [34], and patient or disease registries [35]. For publications in 2010-2019, more data sources were used, including surveys or questionnaire data [12,24,26,, interviews or focus groups [25,27,28,37,69,94,, patient or medical data [23,, clinical or health care research datasets [23,[143][144][145][146][147][148][149][150][151][152][153], patient or disease registries [29,67,154,155], and social media (Facebook [156,157], Twitter [158,159], Quora [22], and WhatsApp [160]) and new social media datasets [161].…”
Section: Publication-based Analysismentioning
confidence: 99%
“…Most studies reported data from a mix of ward types (n = 8), followed by acute wards (n = 6), low/medium secure wards (n = 5), forensic wards (n = 5) and psychiatric intensive care units (PICUs) (n = 3). Only two studies specified that they included wards with inpatients under the age of 18 [48, 63]. The remaining studies either exclusively focused on inpatient wards for adults or did not specify the age of the inpatient populations.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies explored CCTV/video surveillance [39,41,43,48,52,54,55,56,57,58,60,61,63]. No studies declared conflicts of interest, seven studies were rated as high quality [41,43,52,55,56,57,63], three were rated medium quality [48,58,61] and three low quality [39,54,60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation